CO2-selective zeolitic imidazolate framework membrane on graphene oxide nanoribbons: experimental and theoretical studies. Issue 45 (11th November 2021) - Choi, Eunji; Hong, Sung Jun; Chen, Junhe; Kim, Yeong Jae; Choi, Yunkyu; Kwon, Ohchan; Eum, Kiwon; Choi, Ji Il; Jang, Seung Soon; Han, Byungchan; Kim, Dae Woo
Abstract : A CO2 selective ZIF-8 membrane can be fabricated on a graphene oxide nanoribbon coated polymeric support with a CO2 permeance of 7.8 × 10 −9 mol m −2 Pa −1 s −1 and a CO2 /CH4 selectivity of 27. Abstract : A CO2 -selective ZIF-type membrane was fabricated by growing a ZIF-8 layer on a graphene oxide nanoribbon (GONR)-coated polymeric substrate. Owing to the strong anchoring effect of GONRs to the ZIF-8 crystal, the pore window of the ZIF-8 layer can be tuned with a molecular cut-off range of 3.4–3.6 Å. The prepared membrane showed a CO2 permeance of 7.8 × 10 −9 mol m −2 Pa −1 s −1 with a CO2 /CH4 selectivity of 27, which surpassed the CO2 /hydrocarbon separation performance of most reported ZIF-type membranes and were comparable to those of ZIF-94 type membranes known to be effective for CO2 extraction. Multiscale computational simulation demonstrated that the CO2 selective permeation of the ZIF-8/GONR membrane was attributed to the low diffusivity of CH4 in the rigid ZIF-8 framework. The obtained experimental and computational results illustrate that the pore-tuned ZIF-8 framework can be effectively used for CO2 separation by adjusting the aperture size.